Transformational Leadership Model in Improving Accreditation - Fajrin, Meutia (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The accreditation process is one of the important steps to improve the quality of education in educational institutions, including Madrasah Aliyah Swasta. However, many madrasahs face challenges in preparing for accreditation, mainly related to the management of the accreditation team and the quality of the documentation that must be compiled. Principal leadership is considered to have a key role in influencing the success of this process. This study aims to examine the influence of transformational leadership style on accreditation preparation at Madrasah Aliyah Swasta Al-Muslimun. The main focus of the research is the strategies applied by the principal in leading the accreditation team, as well as how these strategies affect the quality of education and teacher performance in the accreditation process. The research method used was qualitative with data collection techniques through interviews, observation and documentation. The results showed that the principal’s transformational leadership plays an important role in creating a positive work culture and improving collaboration between school components. Principals are actively involved in preparing accreditation forms, providing motivation and supporting innovation in education management. In addition, the strategies implemented, such as the preparation of accreditation documents, training for teachers and improvement of facilities, contributed to achieving better accreditation. This research confirms that effective and organized leadership is critical in ensuring the success of the accreditation process in educational institutions. This research is expected to provide insights for school principals and policy makers in designing more effective leadership strategies to support successful accreditation and improved education quality in madrasahs.